2019
DOI: 10.1016/j.ijrobp.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Intensity-Modulated Brachytherapy (IMBT): Static and Dynamic Techniques

Abstract: Purpose: To systematically review scientific literature on the use of intensity-modulated brachytherapy (IMBT), including static and dynamic shielding approaches, to enhance therapeutic ratio. Studies were evaluated for technique, disease site, dosimetry, applicators, dosimetric calculations, and planning algorithms. Comparisons with standard-of-care brachytherapy techniques, alternative IMBT methods, or both were performed for dose-to-target volumes, organs at risk (OARs), and treatment planning or delivery t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 129 publications
(489 reference statements)
0
31
0
Order By: Relevance
“…Both IMRT and VMAT have a good balance benefit/risk in EC compared to conventional conformal RT [ 129 ]. Like EBRT, BT has evolved into intensity-modulated BT (IMBT), 3D and 4D-IGBT, having the same promises and drawbacks as IMRT and IGRT [ 130 ]. Both 3D and 4D-IGBT have shown good local control for women with recurrent EC [ 131 , 132 ] and a 3D-EGBT high response rate in inoperable early stage endometrioid EC [ 133 ].…”
Section: Cutting-edge Advances In Radiotherapy For Endometrial Canmentioning
confidence: 99%
“…Both IMRT and VMAT have a good balance benefit/risk in EC compared to conventional conformal RT [ 129 ]. Like EBRT, BT has evolved into intensity-modulated BT (IMBT), 3D and 4D-IGBT, having the same promises and drawbacks as IMRT and IGRT [ 130 ]. Both 3D and 4D-IGBT have shown good local control for women with recurrent EC [ 131 , 132 ] and a 3D-EGBT high response rate in inoperable early stage endometrioid EC [ 133 ].…”
Section: Cutting-edge Advances In Radiotherapy For Endometrial Canmentioning
confidence: 99%
“…10 For IMBT treatment planning, MC-generated dose distributions are typically used as inputs for the optimization algorithm during inverse optimization. 6 Several detectors have been studied to assess the dose delivery during a brachytherapy treatment. Plastic scintillator detectors (PSDs) show promise for obtaining accurate dose measurements in brachytherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Intensity modulated brachytherapy (IMBT) is a brachytherapy technique that can be delivered using a shielded applicator or source to modulate the dose distribution 6 . Static and dynamic IMBT approaches can be used to modulate the dose distribution to the shape of the tumor, reduce the dose to organs at risk, provide a method for dose escalation, or allow for fewer catheters to be implanted.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the Red Journal, Dr Callaghan and associates provide a systematic review of intensity modulated brachytherapy (IMBT) technology and the state of its development. 1 IMBT, as referred to in the paper, specifies those radiation sources and applicators designs that use metallic shields to create anisotropic "directional" radiation profiles of varying degrees, as opposed to the familiar isotropic dose distribution widely used and described in American Association of Physicists in Medicine TG43, 2 to create brachytherapy plans of high quality. They further categorize IMBT technology into static versus dynamic techniques; if the shield moves during treatment delivery, the technology is classified as the latter as opposed to the former if it is immobile.…”
mentioning
confidence: 99%
“…Since Ebert's paper, there has been tremendous progress in this line of research; numerous and progressive IMBT system designs have been proposed and have shown impressive theoretical benefit in terms of better target coverage (18.6%-71.6%) and decreased normal tissue dose (5.1%-68.2%). 1 2. The brachytherapy field in general has recently seen fast uptake of 3-dimensional imaging (magnetic resonance [MR]/computed tomography/ultrasound) along with perfraction adaptive replanning practice, embracing a true image guided adaptive brachytherapy workflow.…”
mentioning
confidence: 99%